Crisis of empire : doctrine and dissent at the end of late antiquity - Booth, Phil, 1981- (Transformation of the classical heritage ;, 2014)
"This book focuses on the attempts of three ascetics-John Moschus, Sophronius of Jerusalem, and Maximus Confessor-to determine the Church's power and place during a period of profound crisis, as the eastern Roman empire suffered serious reversals in the face of Persian and then Islamic expansion. By asserting visions which reconciled long-standing intellectual tensions between asceticism and Church, these authors established the framework for their subsequent emergence as Constantinople's most vociferous religious critics, their alliance with the Roman popes, and their radical rejection of imperial interference in matters of the faith. Situated within the broader religious currents of the fourth to seventh centuries, this book throws new light on the nature not only of the holy man in late antiquity, but also of the Byzantine Orthodoxy that would emerge in the Middle Ages, and which is still central to the churches of Greece and Eastern Europe"--